Protective role of emodin in rats with post-myocardial infarction heart failure and influence on extracellular signal-regulated kinase pathway - Jinfeng Liu (Taylor & Francis Group, 2021)
We aimed to explore the effects of emodin on the energy metabolism of myocardial cells in rats with post-myocardial infarction (MI) heart failure (HF) and the extracellular signal-regulated kinase (ERK) pathway. The model of MI was established by ligation of the left anterior descending branch. After 4 weeks, the rats with left ventricular ejection fraction (LVEF) of ≤45% were used aspost-MI HF model animals and randomly divided into model, low-dose, middle-dose, high-dose and control groups (n=10). Low-, middle- and high-dose groups were gavaged with 20 mg/kg, 40 mg/kg and 60 mg/kg emodin daily, respectively. After administration for 14 d, the changes in LVEF, left ventricular end-systolic diameter (LVESD), left ventricular end-diastolic diameter (LVEDD) and interventricular septum thickness (IVS) were analyzed. The apoptosis rate of myocardial cells was detected by TUNEL staining. The levels of serum cardiac troponin I (cTnI) and peroxisome proliferator-activated receptor-γ coactivator-1 (PGC-1) were determined using ELISA, and the expressions of mitochondrial respiratory chain complex I protein and phosphorylated-ERK (p-ERK) in myocardial tissues were determined by Western blotting.  Compared with model group, LVEDD, LVESD, apoptosis rate of myocardial cells, levels of serum cTnI and PGC-1, and expressions of complex I and p-ERK in myocardial tissues significantly decreased, while LVEF and IVS increased in low-dose, middle-dose, high-dose and control groups (P<0.05). The changes in the above indices were significantly dependent on the dose of emodin (P<0.05).Emodin can significantly relieve post-MI HF, reduce the apoptosis rate of myocardial tissues, and ameliorate the cardiac function of rats.